Numerical interpretation of whirl flutter in a tiltrotor wind-tunnel model using mid-fidelity aerodynamics and mechanical friction - De Vita, P.; Cassoni, G.; Masarati, P.; Fonte, F.; Favale, M.; Hoff, S.C. van 't (Springer Nature, 2026)
This paper investigates the aeroelastic stability of the ATTILA tiltrotor wind-tunnel testbed through numerical modeling of the system’s advanced dynamic characteristics. Specifically, the study addresses discrepancies between baseline predictions and experimental observations regarding the unexpected sensitivity of flutter modes’ damping to rotor disk tilting. Two enhancements are explored: mid-fidelity aerodynamic modeling using vortex particle methods and mechanical friction modeling in critical joints. Vortex particle free wake and vortex lattice-based modeling for wing aerodynamics significantly improve damping predictions for the out-of-plane bending and torsion modes compared to strip theory approaches for the wing and rotor blades. In contrast, modeling rotor aerodynamics with lifting line and vortex particle free wake only shows marginal improvements. However, aerodynamic enhancements alone cannot reproduce the experimentally observed sensitivity to the gimbal angle. Conversely, introducing friction in specific joints can qualitatively replicate the observed tilt-dependent behavior through stiction-induced joint locking.